Genomic Sequencing Reveals the Diversity of Seminal Bacteria and Relationships to Reproductive Potential in Boar Sperm - Zhang, Jing; Liu, Huan; Yang, Qiangzhen; Li, Peifei; Wen, Yi; Han, Xuejun; Li, Bushe; Jiang, Hongju; Li, Xinhong (Frontiers in Microbiology, 2020)
A number of emerging studies suggest that pathogenic microorganisms in semen may cause a decline in the reproductive potential of spermatozoa, and the bacterial diversity and profile of ejaculated boar semen in different seasons are currently unknown. To explore the bacterial composition and changes in ejaculated boar semen from winter and summer, and the underlying mechanism of decline in sperm quality and fertility capacity in summer, 120 ejaculated semen samples were examined for bacterial communities using genomic sequencing technology, and the associations between microbial composition and sperm reproductive potential were investigated. The results showed that Proteobacteria (57.53%), Firmicutes (31.17%), Bacteroidetes (4.23%), and Actinobacteria (3.41%) are the dominant phyla in the ejaculated semen, and the dominant genera were Pseudomonas (34.41%) and Lactobacillus (19.93%), which belong to the phyla of Proteobacteria and Firmicutes, respectively. Interestingly, the higher diversity of bacteria in ejaculated semen of winter differs from that of summer semen, potentially due to seasonal changes related to changes in semen quality and sperm fertilizing capacity. Furthermore, the highly abundant Lactobacillus in winter samples were positively associated with sperm quality and reproductive performance obtained from sows inseminated with such semen samples, while in contrast, the highly abundant Pseudomonas in summer samples was negatively associated with sperm quality and reproductive potential. Additionally, our results strongly indicated that Lactobacillus is not only a potential probiotic for semen quality and fertility potential but also beneficial for restraining the negative influence of Pseudomonas. Overall, our findings significantly contribute to the current understanding of the phenotypes and etiology of male “summer infertility”, and may represent a frontier in male reproductive disorders and possible early prevention against pathogenic bacteria.